Self-Acceptance Ibu yang Memiliki Anak Berkebutuhan Khusus (Down Syndrome) - Muhammad Iqbal; Adinda Yuniesya; Genta prasetya; Reris Yumi Febriani; Yodi Kasinda; Nurmina Nurmina (CV. Rumoh Aceh Publishing, 2026)
Every parent wants a child to be present in their home. All parents hope that their children will be born perfect. Parents want their children to be physically and mentally healthy. However, some children are born and grow in abnormal conditions. Some of them have physical and mental limitations since birth. This research aims to determine the extent of self-acceptance of parents who have children with special needs, especially children with Down syndrome. The method used in this research is a qualitative approach with the phenomenological method. The data analysis technique used was Interpretative Phenomenological Analysis (IPA) with purposive sampling technique in selecting subjects. The data collection method in this research was in-depth semi-structured interviews with three mothers who have children with Down syndrome. In this research, three main themes were found, namely (1) Parental emotional- psychological experiences, (2) Parenting strategies, (3) Positive experiences, as well as five special themes, namely (1) Self-surrender, (2) Self-introspection, (3) ) Openness, (4) Input from other people, and (5) Your contribution. The results of this research show that the process of self-acceptance for mothers who have children with Down Syndrome is a long and complex journey, involving various emotional and adaptation stages. Mothers of children with special needs face significant emotional challenges, including shock, sadness, worry, and pressure from society. This research also emphasizes the importance of emotional support, openness, and wise parenting strategies in helping mothers accept and care for children with Down Syndrome.